الشكلية في بيع المحل التجاري - - بلحو حسين (المسيلة, 2022)
يعتبر عقد البيع الوارد على المحل التجاري من العقود الهامة ،نظرا للمكانة المعتبرة التي يحتلها، وكذا تمتعه بطبيعة خاصة باعتباره مال منقول معنوي يصعب إخضاعالتصرفات الواردة عليهلأحكام القانون المدني فقط، ومن بين هذه الأحكام القانونية نجد الشكلية، هذه الأخيرةنجد المشرع التجاري قد خصها بجملة من القواعد التي تنظمها،وتأطرها وفق قواعد خاصة في القانون التجاري وقواعد أخرئ عامة واردة في القانون المدني ،كما أن لها الدور الكبير في بيع المحل التجاري باعتبار الشكلية وسيلة لتحقيق غاية تتمثل في حماية المتعاقدين والدائنين، بالإضافة إلى مبدأي الثقة والائتمان التي يتطلبها عالم التجارة. الكلمات المفتاحية : الشكلية – المحل التجاري – القانون التجاري – بيع المحل التجاري –البائع – المشتري. Summary : The contract of sale on the commercial shop is considered one of the important contracts, given the considered position it occupies, as well as its special nature as it is a moral movable property that is difficult to subject the incoming actions to the provisions of the civil law only, and among these legal provisions we find the formality, the latter we find the commercial legislator has singled out it With a set of rules that regulate it, and frame it according to special rules in commercial law and other general rules contained in civil law, it also has a great role in selling the commercial shop considering the formality as a means to achieve an end represented in the protection of contractors and creditors, in addition to the principles of trust and credit required by the world of commerce . Keywords: formality - commercial shop - commercial law - sale of commercial shop - seller - buyer.
Keywords: – المحل التجاري – القانون التجاري – بيع المحل التجاري –البائع – المشتري.